Uma experiência de ensino do futebol no currículo de licenciatura em Educação Física - experiência nº 2 - Vicente Molina Neto (Universidade Federal do Rio Grande do Sul, 2000)
This work presents the results of a qualitative investigation carried out in physical education classes in the public schools of the city of Porto Alegre -RS. The purpose of the study was to examine the relationship between the production of knowledge in physical education and the professional practice of future physical education teachers. The research focused on the teaching of a specific element of the Brazilian physical culture (soccer) to students of 5th to 8th grades during a period of an academic term by 11 final year undergraduate students of the Faculty of Physical Education of the Federal University of Rio Grande do Sul. With reference to the organization of the curriculum, the investigation showed the need to review the material conditions for which the high education institutions organize the pedagogic work of the future professionals. For the latter, the accomplished work was a councious immersion in the environment of the Public School, especially in respect to the establishment of a teaching programme in accordance with the social conditions of the school and group. The research also showed that the professional training was disconnected from the school needs. Finally, the difficulty of the future professionals to carry out a research during the educational activity showed the incongruity between the production of knowledge and the fundamental questions posed by the practice of physical education teachers in school.